2015
DOI: 10.13165/siiw-15-1-1-03
|View full text |Cite
|
Sign up to set email alerts
|

The Grass is Greener: How Greenery Impacts the Perceptions of Urban Residential Property

Abstract: Can different types of greenery improve the perceived value, safety, prestige, coziness, and aesthetics of multistory residential buildings?<br />To find the answer, two studies were carried out. In Study 1, participants filled in questionnaires designed to measure the perceived value,<br />safety, prestige, coziness, and aesthetics of a building. Every questionnaire was accompanied with one of four images of the same residential building, the only difference between them was the type of greenery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The preference for new greenery was largely in line with the provision of manicured space, by indicating flowerbeds and neat lawns. A preference for such tidy formal features was also found in other studies (Özünger & Kendle, 2006;Poškus & Poškienė, 2015;Sikorski et al, 2018); additionally, it was shown that the presence of flowers clearly increases the attractiveness of UGS in many cases (e.g. Lee, Williams, Sargent, Farrell, & Williams, 2014;Lindemann-Matthies & Brieger, 2016;Todorova, Asakawa, & Aikoh, 2004).…”
Section: Suggestions For Design Interventionssupporting
confidence: 77%
“…The preference for new greenery was largely in line with the provision of manicured space, by indicating flowerbeds and neat lawns. A preference for such tidy formal features was also found in other studies (Özünger & Kendle, 2006;Poškus & Poškienė, 2015;Sikorski et al, 2018); additionally, it was shown that the presence of flowers clearly increases the attractiveness of UGS in many cases (e.g. Lee, Williams, Sargent, Farrell, & Williams, 2014;Lindemann-Matthies & Brieger, 2016;Todorova, Asakawa, & Aikoh, 2004).…”
Section: Suggestions For Design Interventionssupporting
confidence: 77%
“…Recent studies from Europe and USA have revealed that people's love of lawns is connected to the integral role lawns play in the everyday landscape [1,22,[60][61][62][63]71,72]. Short cut lawnscapes are associated with improved quality of life and personal safety.…”
Section: Cultural Services Of Lawns: Recreationmentioning
confidence: 99%